Partial hydrogenation of soybean oil using metal-decorated integral-asymmetric polymer membranes: Effects of morphology and membrane properties - Singh, D.; Rezac, Mary E.; Pfromm, Peter H. (My University, 2010)
Three phase reaction schemes pose numerous challenges to reactor design due to the slow diffusional mass transfer of reactants from the gas phase through a liquid to the active sites of the catalyst. An example is partial hydrogenation of vegetable oil which is traditionally carried out in a batch autoclave by bubbling hydrogen gas though a slurry of oil and solid catalyst particles containing Ni. Unwanted trans fatty acids (TFAs) are formed during this process due to the scarcity of hydrogen at the active catalyst sites. Here we investigate the use of metal-decorated integral-asymmetric polymer membranes to enable the supply of dissolved hydrogen near the location where the liquid oil phase contacts the catalyst. Hydrogen gas is supplied to the porous substructure of the asymmetric membrane where it dissolves in the thin skin layer of the membrane and emerges as dissolved hydrogen on the metal-decorated side of the membrane where the oil is present. Temperature and pressure are compatible with existing facilities. All membranes produced low TFA (2.6–4.6 wt% at Iodine Value of 95) compared to the slurry process. A 1000 metric ton per day soybean oil hydrogenation facility would require 2–3000 m[superscript]2 membrane area with a total of 90 g of Pt metal catalyst. This could be envisioned as metal sputtered hollow fibers packaged in conventional modules.
Keywords: Membrane reactor; Trans fatty acid; Soybean oil; Partial hydrogenation; Integral-asymmetric; Metal polymer membranes